2005
DOI: 10.5194/aab-48-359-2005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of breed cross on performance and meat quality of once-bred gilts in a seasonal outdoor rearing system

Abstract: Abstract. This study investigated the suitability of once-bred gilts of two different breed crosses in an alternative seasonal outdoor rearing system, with slaughter of the once-bred gilts and their progeny at the end of the season. In total 38 once-bred gilts (Large White x Landrace (LW*L) and Large White x Duroc (LW*D) were housed outdoors one month before farrowing until slaughter, 2-3 weeks after weaning. Body weight, backfat thickness and litter size of the once-bred gilts, and pre-weaning mortality and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…The results of the current study may indicate that Duroc crosses are more suitable for outdoor production because they have significantly more backfat at weaning than the crosses of Landrace and Yorkshire. This is in accordance with Heyer et al (2005) who hypothesised that the lower weight loss during lactation is due to a lower litter size, as also found in the current study, in addition to a higher feed consumption during lactation. The higher backfat at weaning together with a higher growth rate before (Heyer et al, 2005) and after weaning (Stern et al, 2003) in Duroc crosses might counteract the potential negative impact on the production economy caused by lower litter sizes.…”
Section: Backfat Thickness At Weaningsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of the current study may indicate that Duroc crosses are more suitable for outdoor production because they have significantly more backfat at weaning than the crosses of Landrace and Yorkshire. This is in accordance with Heyer et al (2005) who hypothesised that the lower weight loss during lactation is due to a lower litter size, as also found in the current study, in addition to a higher feed consumption during lactation. The higher backfat at weaning together with a higher growth rate before (Heyer et al, 2005) and after weaning (Stern et al, 2003) in Duroc crosses might counteract the potential negative impact on the production economy caused by lower litter sizes.…”
Section: Backfat Thickness At Weaningsupporting
confidence: 94%
“…This is probably because the nursing frequency (Wallenbeck et al, 2008) and milk production (Walker & Young, 1992) have already decreased markedly after 5Á6 weeks coinciding with an increase in the piglets' intake of solid feed (Pajor et al, 1999;Damm et al, 2003). Heyer et al (2005) similarly observed that sows housed outdoors had a significant loss of backfat from farrowing to five weeks in lactation, but even had a small gain in backfat from five weeks to weaning four weeks later.…”
Section: Backfat Thickness At Weaningmentioning
confidence: 99%
“…Sow feed consumption the first 14 days pp was estimated to 65% of the recommended feed intake. Heyer et al (2005) also found a low feed intake during the first 10 days pp, 76% of the recommended feed intake for Yorkshire × Landrace primiparous gilts farrowing outdoors. The low feed consumption in this environment might be because the sow has to leave the hut and her piglets to get to the feed trough.…”
Section: Discussionmentioning
confidence: 87%
“…Further, a sufficient total daily intake of protein and amino acids could probably be assured by using ad libitum feeding. However, the diet should have a lower energy density than used conventionally in order not to compromise the carcass quality (MICKLICH et al, 1999;HEYER et al, 2005). In the present experiment pigs received recommended (R), 7 % lower (R-7) or 14 % lower (R-14) levels of amino acids, in a phase feeding system with a low-energy diet provided ad libitum.…”
Section: Introductionmentioning
confidence: 93%